The effect of microlearning educational intervention on communication skills of nurses working in Shiraz Trauma Hospital in 2021 - Zahra keshtkaran; Fatemeh Dadgar; Zahra karimian; Rasoul Raesi; Jalal kavoosi (Journal of Education and Health Promotion)
Background: Nursing is one of the groups that spends more time with patients. Therefore, communication skills are essential for providing comprehensive care and establishing effective relationships. This study was conducted to investigate the effect of microlearning educational intervention on communication skills of nurses. Materials and Methods: This quasi-experimental study was conducted in 2021 by convenience sampling. A total of 197 nurses working in Shiraz Martyr Rajaei Trauma Hospital were enrolled in the study. The educational content in this study included multimedia educational content that was made available to nurses through communication software. The data collection tool consisted of two questionnaires, including a demographic information questionnaire and a queen’s communication skills questionnaire. The data were analyzed using SPSS version 25, and the significance level was set at 5%. Results: Most of the participants in the research were female (70.1%), in the age group of 25–35 years. The scores of the main variables of communication skills, including the ability to receive and send messages, emotional control, listening skills, insight into the communication process, communication skills with certainty, and the total score of communication skills, showed a statistically significant difference before and after the intervention (P value < 0.05). Conclusion: Microlearning intervention through multimedia education can be an effective method for improving the communication skills of nurses working in hospital settings. Increasing nurses’ awareness of communication skills is also essential, and it is recommended that this training be provided to nurses periodically to promote the nursing profession, especially using microlearning interventions.